Air-Surveyed Cropmarks of Early Iron Age Heritage in Central Europe—Integrating Remotely Detected Data and Excavated Evidence - Gojda, Martin; Trefny, Martin; Schussmann, Markus; Šumberová, Radka (Heritage, 2022)
This paper aims to present the potential of observations of the Earth’s surface by means of remote sensing (survey), specifically via direct (active) visual prospection from low altitude to identify and map small components (such as postholes) of archaeological contexts, namely aboveground post-built structures dated to the Early Iron Age (appr. 800–380 B.C.). This work gives an example of archaeological data on buried settlement constructions identified by aerial reconnaissance (i.e., by a non-invasive method), the interpretation—and primarily dating—of which is based on information achieved by excavation practice (recently performed predominantly during rescue campaigns). This research points to the fact that nonetheless to the traditional idea on the limited potential of crop-marked archaeological heritage in terms of dating (the ability of cropmarks displayed over pits, ditches, graves, etc., to produce exact ground-plans of even small buried features, so that their original function and dating can be determined) the number of more or less precisely datable archaeological sites and features buried under the surface is growing, including wooden structures once constructed on the ground (i.e., not sunken under the ground) and leaving on cereal crops just tiny spots/dots regularly spaced into lines. These are features (constructions) with identical ground plans (postholes placed in 4 × 3 and/or 3 × 3 patterns) of which commonly just one in a group of them situated on one site is enclosed by a perimeter line—a foundation for a wall or a trench for a palisade. Consequently, a retrospective survey of air-photo analog archives and digital repositories now brings new evidence on the chronological setting of many crop-marked Early Iron Age sites that previously remained undated.
CRIS-Team Scopus Importer:2022-04-29
Keywords: archaeological remote sensing; Central Europe; cropmarks; Early Iron Age settlements; excavation-based dating; post-built structures